Pemanfaatan Alat Dispenser Pakan Ikan Otomatis Berbasis Internet Of Things oleh Kelompok Masyarakat Kaweruan Kabupaten Minahasa Utara dalam Meningkatkan Efektivitas dan Produktivitas Budidaya Ikan Mujair - Ryan Laksmana Singgeta; Ignatia R. Honandar; Pinrolinvic D. K. Manembu (LPPM STIKOM Tunas Bangsa, 2022)
Freshwater fish farming is a leading commodity and an economic driver in North Minahasa Regency which is being developed and improved by the local government. This is a very big opportunity for community groups who wish to earn a fortune through freshwater fish farming. Community groups who are proposing partners have started cultivation activities, especially tilapia fish since 2019. Some of the problems faced by these groups lie in the effectiveness of fish farming, especially in the conventional fish feeding process. Where fish feeding is still fully supervised and carried out by the cultivation group so that it is considered less effective and efficient. For this reason, the team implemented an Internet of Things-based Automatic Fish Feed Dispenser Tool. This activity program uses a training and mentoring method approach including: training on tilapia fish cultivation; preparation of financial reports and design of automatic feed dispensers. Based on the evaluation results, in general, community groups are able to directly practice appropriate and appropriate tilapia fish cultivation, are able to understand the preparation of financial reports and how to manage simple cash inflows and outflows and the team can design an Automatic Fish Feed Dispenser Tool. The tools that have been designed can work properly, which can increase the effectiveness of tilapia fish farming.